Biomaterials: So Many Choices, So Little Time. What Are the Differences? - Hunter, John D., III; Cannon, Jamie A. (Clinics in Colon and Rectal Surgery, 2014)
The use of biologic mesh has increased greatly in recent years in response to the need for a solution in managing contaminated hernias. Multiple different meshes are commercially available, and are derived from a variety of sources, including human dermis as well as animal sources. For a mesh to be effective, it must be resistant to infection, have adequate tensile strength for hernia repair, and be well tolerated by the host. To achieve this end, biologic meshes go through an intense processing that varies from one product to the next. In this article, the authors review the types of mesh available, how they are processed, and examine these characteristics in terms of their strengths and weaknesses in application to surgical technique.
Keywords: biologic mesh; cross-linking; xenograft; ventral hernia